2020
DOI: 10.1111/odi.13722
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intensive oral care before surgery for gastric cancer patients

Abstract: Objectives: Oral function management has been recognized as important strategy for preventing postoperative complications. In this historical cohort study, we focused on the patients who planed gastrectomy, and investigated the appropriate duration and frequency of preoperative oral care to prevent complications after surgery. Methods: Patients who planed surgery for gastric cancer between 2012 and 2018 were enrolled. We defined intensive oral care (IOC) as initial intervention at least three weeks before surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…There was one randomized controlled trial (RCT) and seven observational studies [20] , [21] , [22] , [23] , [24] , [25] , [37] , [38] , [39] . The RCT [20] reported significantly less postoperative increase in lung murmurs, but no significant difference in increased body temperature (risk of bias was high).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was one randomized controlled trial (RCT) and seven observational studies [20] , [21] , [22] , [23] , [24] , [25] , [37] , [38] , [39] . The RCT [20] reported significantly less postoperative increase in lung murmurs, but no significant difference in increased body temperature (risk of bias was high).…”
Section: Resultsmentioning
confidence: 99%
“…The RCT [20] reported significantly less postoperative increase in lung murmurs, but no significant difference in increased body temperature (risk of bias was high). In the observational studies, five studies [22] , [23] , [24] , [25] , [37] examined the frequency of postoperative SSI between patients with and without perioperative oral management, and all reported a significantly lower frequency of SSI in the patients with perioperative oral management than without (risk of bias was low in all studies). Nishikawa et al [39] examined the association between SSI and periodontal disease status in patients who underwent perioperative oral management and found that severity of periodontal disease was a significant risk factor for SSI.…”
Section: Resultsmentioning
confidence: 99%
“…A statistically significant association was found between preoperative oral care and a decrease in postoperative pneumonia and all-cause mortality in the first 30 days after surgery [ 59 ]. Moreover, before resection surgery for gastric cancer, patients that received intensive oral care prior to the intervention had a decreased risk of developing postoperative infectious complications [ 29 ]. However, if nurses receive education and training in order to successfully implement oral hygiene procedures, this could result in a healthier oral status, which translates in fewer cases of hospital-acquired pneumonia [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of home care, another study stated that more than half of the caregivers were helping patients with nutrition, taking medication, or changing clothes, but just 26% helped the patients with oral hygiene [ 27 , 28 ]. A recent paper showed that patients who received oral care before the resection surgery of gastric neoplastic tissue had diminished risk of developing postoperative complications [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative oral management (POM) contributes to prevention and reduction of complications in cancer surgery. [1][2][3][4][5] It is especially effective in reducing morbidities, such as respiratory infection and surgical site infection, as well as reducing the length of hospital stay and mortality rate. 6 POM was introduced into the Japanese universal health insurance system in 2012.…”
Section: Introductionmentioning
confidence: 99%